Antitumor Effects of Evodiamine in Mice Model Experiments: A Systematic Review and Meta-Analysis - Yin, Cong; Cheng, Jing; Peng, Hongbing; Yuan, Shijun; Chen, Keli; Li, Juan (Frontiers in Oncology, 2021)
Abstract Background: Evodiamine (EVO), an alkaloid extracted from the traditional Chinese medicine Euodia rutaecarpa, plays an important role in the treatment of cancer. This study was performed to clarify the effects of evodiamine in mice tumor model studies. Methods: Electronic databases and search engines involves China Knowledge Resource Integrated Database (CNKI), Wanfang Database, Chinese Scientific Journal Database (CSJD-VIP), China Biomedical Literature Database (CBM), PubMed, Embase, Web of Science, and ClinicalTrials.gov databases, which were searched for literature related to the anti-tumor effects of evodiamine in animal tumor models (all until 1 October 2021). The evodiamine effect on the tumor volume and tumor weight were compared between the treatment and control groups using the standardized mean difference (SMD). Results: Evodiamine significantly inhibited tumor growth in mice, as was assessed with tumor volume [13 studies, n=267; 138 for EVO and 129 for control; Standard mean difference (SMD)= -5.99; 95% (CI): -8.89 to -3.10; I2 = 97.69%, p≤0.00], tumor weight [6 studies, n=89; 49 for EVO and 40 for control; Standard mean difference (SMD)= -3.51; 95% (CI): -5.13 to -3.90; I2 = 83.02%, p≤0.00]. Conclusion: EVO significantly suppress tumor growth in mice models, which would be beneficial for clinical transformation. However, due to the small number of studies included in this meta-analysis, the experimental design and experimental method limitations should be considered when interpreting the results. Significant clinical and animal studies are still required to evaluate whether EVO can be used in the adjuvant treatment of clinical tumor patients.